The Role of Intellectual Capital on Firm Value Mediated by Corporate Governance - Wijaya, Antoro (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
This study uses a quantitative approach, in determining the sample of this study using non-probability sampling method with purposive sampling technique. The research data obtained were 21 consumer goods companies listed on the Indonesia Stock Exchange for the period 2015-2017, so the data obtained were 63. The data obtained were analyzed through outer and inner model tests, as well as hypothesis testing in PLS analysis. The results revealed that Intellectual Capital has an effect on Firm Value. There is an influence of Intellectual Capital on Corporate Governance. There is an influence of Corporate Governance on Company Value. And there is an influence of Intellectual Capital on Firm Value through Corporate Governance..